EVALUATION OF THE USE OF BIM METHODOLOGY IN ENGINEERING AND ARCHITECTURAL OFFICES: A LITERATURE REVIEW (REMUNOM, 2024)
The need for ease and agility in civil construction projects is a reality today. Building Information Modeling (BIM) is a tool that brings improvements to the areas of civil engineering and architecture. The objective of this work is to evaluate the use of the BIM methodology in engineering and architecture offices, through a literature review. The study showed the advantages and obstacles of using and implementing BIM. Through the results obtained, it was possible to conclude that BIM already has a high level of acceptance regarding its use, providing agility in projects and avoiding possible errors. However, there is still a certain limitation regarding the implementation of the method, due to the high cost of acquiring the programs and lack of specialized professionals.